Transformation of Village Digital Governance through Digital Literacy Education Program in the Implementation of Smart Villages in Indonesia - Sugiartini, Pegi (Politeknik Siber Cerdika Internasional, 2025)
The digital transformation of village governance is essential for the successful implementation of Smart Village initiatives in Indonesia. Despite the government’s efforts, challenges remain, including low digital literacy among village officials and infrastructure limitations. This study aims to explore how village leadership drives digital transformation through digital literacy education programs within the Smart Village framework. A mixed-methods approach was employed, combining quantitative surveys with qualitative case studies across 45 villages in Indonesia. The research identifies the significant role of transformational leadership in facilitating digital governance, showing that leaders who actively engage with and support digital literacy programs achieve higher participation and completion rates. Key findings reveal that digital literacy programs significantly improve village administrative capacity, including data management, e-governance, and transparency. The research highlights leadership competencies, such as vision articulation and stakeholder mobilization, as critical drivers of success. The study concludes that leadership-driven digital literacy education is crucial for bridging the digital divide, enhancing governance efficiency, and ensuring the sustainability of Smart Village initiatives. Recommendations include investing in leadership development and tailored digital literacy programs to foster inclusive digital transformation in rural areas.